Membentuk Karakter Siswa Melalui Keteladanan Guru - Nurchaili -- (Jurnal Pendidikan dan Kebudayaan, 2010)
The government made an effort to solve moral decadence problem by proclaiming â€œ CharacterÂ Educationâ€ in every level of education. Character education is a holistic educational process that connects the moral dimension to the social realm in the students life as the foundation to establish quality generations who are able to live independently and have the truth principle that can be accounted for. Character is a â€œbehaviorâ€ not a â€˜knowledgeâ€™. So, in the practice of character education requires not only the theory or the concept its self, but also the direct model of the teacher. Therefore, it can be internalized by the students well because it is not only taught but also exemplified. The implementation of character education in schools is more accurate through modeling approaches, modeling (uswah) conducted by the teacher Teacherâ€™s exemplary is needs to be created because a teacher is a central figure in th school that the studentsâ€™ attention always for them. Teachers should really be an example not only the conveyor of science information, but also includes transferâ€™s activity of virtuous noble character personality in order to form studentâ€™s character as a national asset that will be the determinant of the existence of this nation.Â ABSTRAKÂ Pemerintah berusaha menyikapi permasalahan dekadensi moral atau merosotnya karakter peserta didik dengan mencanangkan pendidikan karakter disetiap jenjang pendidikan. Pendidikan karakter merupakan suatu proses pendidikan secara holistik yang menghubungkan dimensi moral dengan ranah sosial dalam kehidupan peserta didik sebagai pondasi bagi terbentuknya generasi yang berkualitas yang mampu hidup mandiri dan memiliki prinsip kebenaran yang dapat dipertanggungjawabkan. Dalam praktiknya pendidikan karakter tidak hany membutuhkan teori atau konsep semata. Karakter merupakan perilaku (behaviour), bukan pengetahuan sehingga untuk dapat diinternalisasi oleh peserta didik, maka harus diteladankan bukan hanya diajarkan. Pelaksanaan pendidikan karakter di sekolah lebih tepat melalui pendekatan modeling, keteladanan (uswah) yang dilakukan oleh guru. Keteladanan guru perlu diciptakan karena gurulah sebagai tokoh sentral yang setiap saat menjadi perhatian peserta didik di sekolah. Guru harus benar-benar menjadi teladan bukan hanya sebata penyampai informasi ilmu pengetahuan, melainkan meliputi kegiatan mentransfer kepribadian yang berbudi pekerti luhur guna membentuk karakter peserta didik sebagai aset bangsa yang akan menjadi penentu eksistensi bangsa ini.